Smooth speed control of permanent magnet servo systems using artificial neural network - Wang, Shuoyuan (Nanyang Technological University, 2023)
The project aims to develop a high-performance speed controller for servo systems. In servo applications, the development of high-performance speed controller has been accelerated. The speed controller has to offer high precision, good tracking performance, nice disturbance rejection property, and strong robustness to parameter variations. As a model-free control method, artificial neural network (ANN) based control can enhance the anti-disturbance rejection ability and has a strong robustness to parameter variations. This project allows student to develop an ANN based high-performance speed controller from design, analysis, simulation and evaluation. Exceptional design can be made as experimental prototype for concept verification.